The role of prison nursing: an integrative review - A Isaac Caro (Sociedad Española de Sanidad Penitenciaria, 2021)
Abstract Objectives To review the scientific literature on the role of the nurse in Penitentiary Institutions through the study of care training and ethical implications when offering quality care to the prison population. Material and method An integrative review was carried out in Medline, SciELO and LILACS databases. The MeSH and DeCS terms used were: nurse's role, nursing, nurse, nursing education, prison, ethics, ethical issues, job satisfaction, enfermería, penitenciaria, health professionals, nursing care. The types of studies included in this work are literature reviews, and qualitative, quantitative and mixed studies. The CASPe tool was used to assess the methodological quality of selected literature. The review period was October, November and December 2019. Results A total of 264 articles were obtained, of which 98 were chosen after applying filters corresponding to each database and after discarding duplicate articles. The title and abstract of these articles were read and the established selection criteria were applied, to obtain 18 studies. Finally, after critical reading, 15 articles were selected for this work. Discussion The role of the prison nurse is generally unknown. Nursing undergraduate training in this area is limited, exposing a specific training need, which may help these professionals to deal with ethical issues that they may find in their practice, as well as to improve the quality of care for the prison population.